2008
DOI: 10.1080/03079450802272952
|View full text |Cite
|
Sign up to set email alerts
|

Use of polymerase chain reactions to detectMycoplasma gallisepticum,Mycoplasma imitans,Mycoplasma iowae,Mycoplasma meleagridisandMycoplasma synoviaein birds of prey

Abstract: Certain Mycoplasma spp. are pathogens of poultry, but little is known of the role of mycoplasmas in disease of birds of prey. Species-specific polymerase chain reactions (PCRs) for the detection of the poultry pathogens Mycoplasma gallisepticum, Mycoplasma imitans, Mycoplasma iowae, Mycoplasma meleagridis and Mycoplasma synoviae were therefore evaluated for use in birds of prey. The specificities of the PCR methods were established using avian and other mycoplasmas and also selected walled bacteria. The sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 27 publications
1
22
0
1
Order By: Relevance
“…The local chickens appeared normal without any obvious clinical signs. This result was similar to the findings of previous authors (Carpenter et al, 1981;Lierz et al, 2000;Lierz et al, 2002;Lierz et al, 2008;Peebles et al, 2004) who found high seroprevalence of Mycoplasma in birds of prey even though the adult birds remained clinically normal. This can be attributed to the type of husbandry system practiced by the villagers and including lack of vaccination of local chickens and non-existence of mycoplasma control program in Nigeria.…”
Section: Discussionsupporting
confidence: 93%
“…The local chickens appeared normal without any obvious clinical signs. This result was similar to the findings of previous authors (Carpenter et al, 1981;Lierz et al, 2000;Lierz et al, 2002;Lierz et al, 2008;Peebles et al, 2004) who found high seroprevalence of Mycoplasma in birds of prey even though the adult birds remained clinically normal. This can be attributed to the type of husbandry system practiced by the villagers and including lack of vaccination of local chickens and non-existence of mycoplasma control program in Nigeria.…”
Section: Discussionsupporting
confidence: 93%
“…The complete genome sequence of M. iowae has been published recently (Wei et al, 2012) and reveals the presence of two rRNA operons, which may help to explain why the sensitivity can be less than one organism per reaction. This detection limit is similar to that obtained by Lierz et al (2008) who detected as little as 0.1 CFU, and is lower than the 3.2 CFUs per PCR reaction found by Cai et al (2008) or the 10 colour changing units per reaction reported by Laigret et al (1996). Zhao & Yamamoto (1993) could detect 1 pg of M. iowae DNA, while Boyle et al (1995) and Kempf et al (1994) did not assess the amount of DNA or count the CFUs.…”
Section: Discussionmentioning
confidence: 56%
“…Several of the PCR assays described for M. iowae have been based on the 16S rRNA gene (Kempf et al, 1994;Boyle et al, 1995;Kiss et al, 1997;Cai et al, 2008;Lierz et al, 2008) although two (Laigret et al, 1996;Raviv & Kleven, 2009) targeted a region upstream of the rRNA operon. The forward primer of the PCR assay described in this paper is based on the ISR between the 16S and 23S rRNA genes and the reverse primer on the 5?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, some MG species-specific PCR, MG realtime PCR, PCR-RFLP and oligonucleotide probe techniques are available (Callison et al, 2006;Jarquin et al, 2009;Kahya et al, 2010;Lierz et al, 2008;Mardassi et al, 2005;Raviv et al, 2008;Sprygin et al, 2010). During the acute stage of the infection the number of MG in the upper respiratory tract is high, but in chronic infection the number of organisms is much lower and routine methods may not detect it (Levisohn and Kleven, 2000).…”
Section: Discussionmentioning
confidence: 99%